Novel method for transaxillary Impella 5.0 implantation in patients with tortuous arterial anatomy. Issue 7 (19th July 2021) - Fisher, Bryant; Smith, Conrad; Sultan, Ibrahim; Kilic, Arman
Abstract: A novel method of transaxillary Impella 5.0 implantation utilizing a vascular sheath can overcome difficult arterial anatomy and provide mechanical support for patients in critical cardiogenic shock. Abstract : A novel method of transaxillary Impella 5.0 implantation utilizing a vascular sheath can overcome difficult arterial anatomy and provide mechanical support for patients in critical cardiogenic shock.